KETENTUAN PERALIHAN DALAM PERATURAN PERUNDANG-UNDANGAN - Hariningsih, Sri (Jurnal Legislasi Indonesia, 2009)
Transitional provision is one of provision in the legislations that itsformulation is defined “when required or if needed”. This definition meansthat not all legislations have transitional provision. Transitional provisionis needed to prevent any legal vacuum condition due to change of a provisionin the legislation. Change of provision, among other things is related to acondition like division of territory, expansion of territory, transition ofauthority from one institution to another institution or transition of courtjurisdiction. Transitional provision often be formulated confused with closingprovision.